The Morris Worm at 30. (13th February 2019) - Furnell, Steven; Spafford, Eugene H
Abstract: Steven Furnell, University of Plymouth UK, and Eugene H. Spafford, Purdue University USA, turn the clock back 30 years and show that, though bigger, the internet might not be much safer.